2016
DOI: 10.1002/jmor.20556
|View full text |Cite
|
Sign up to set email alerts
|

Dual secretion locations on type II cells in the avian lung suggest local as well as general roles of surfactant

Abstract: Transmission electron microscopy indicates that the avian lung surfactant may be secreted in two directions: a) into air passages of parabronchus, atrium and infundibulum where it forms a trilaminar substance serving the respiratory role and b) to the basolateral surface-intercellular space-of type II pneumocytes, contributing to the innate and adoptive immune responses of lung. Basolateral secretion may be confirmed by the presence of trilaminal substance in the intercellular space of type II pneumocytes. Fus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…While its possible role in defence has not been directly investigated in bird lungs (Van Iwaarden et al, 1990;Lorz & L opez, 1997;Kunchala et al, 2023), in the mammalian lung, together with functions such as reduction of surface tension (Van Golde, Batenburg & Robertson, 1988) and prevention of exudation of blood plasma onto the respiratory surface (Leiby, Raredon & Niklason, 2020), the surfactant provides an important defence function of destroying pathogenic microorganisms (Wright, 1997(Wright, , 2003Wu et al, 2003Wu et al, , 2021. For the lungs of the chicken, Stearns et al (1987) observed that inhaled particles were first trapped by the trilaminar substance, a special kind of avian pulmonary surfactant (Pattle, 1958;Tyler & Pangborn, 1964;Jones & Radnor, 1972;Scheuermann et al, 1997;B odi et al, 2016), and then moved across the epithelium to the underlying interstitial/subepithelial (tissue/fixed) macrophages and even across the BGB to be phagocytosed by the pulmonary intravascular macrophages (PIMs). The air sacs of the avian respiratory system are poorly vascularized, delicate and transparent (McLelland, 1989;Maina, 2005): the inner wall is predominantly lined by a simple squamous epithelium supported by a thin layer of connective tissue and scattered ciliated columnar cells that are located close to the ostial connections (Fletcher, 1980;McLelland, 1989;Crespo, Yamashiro & Hunter, 1998).…”
Section: Pulmonary Airway Mucosal Defencesmentioning
confidence: 99%
See 2 more Smart Citations
“…While its possible role in defence has not been directly investigated in bird lungs (Van Iwaarden et al, 1990;Lorz & L opez, 1997;Kunchala et al, 2023), in the mammalian lung, together with functions such as reduction of surface tension (Van Golde, Batenburg & Robertson, 1988) and prevention of exudation of blood plasma onto the respiratory surface (Leiby, Raredon & Niklason, 2020), the surfactant provides an important defence function of destroying pathogenic microorganisms (Wright, 1997(Wright, , 2003Wu et al, 2003Wu et al, , 2021. For the lungs of the chicken, Stearns et al (1987) observed that inhaled particles were first trapped by the trilaminar substance, a special kind of avian pulmonary surfactant (Pattle, 1958;Tyler & Pangborn, 1964;Jones & Radnor, 1972;Scheuermann et al, 1997;B odi et al, 2016), and then moved across the epithelium to the underlying interstitial/subepithelial (tissue/fixed) macrophages and even across the BGB to be phagocytosed by the pulmonary intravascular macrophages (PIMs). The air sacs of the avian respiratory system are poorly vascularized, delicate and transparent (McLelland, 1989;Maina, 2005): the inner wall is predominantly lined by a simple squamous epithelium supported by a thin layer of connective tissue and scattered ciliated columnar cells that are located close to the ostial connections (Fletcher, 1980;McLelland, 1989;Crespo, Yamashiro & Hunter, 1998).…”
Section: Pulmonary Airway Mucosal Defencesmentioning
confidence: 99%
“…By serving as antigen-presenting cells, DCs regulate innate and adaptive immune responses (Albert, Sauter & Bhardwaj, 1998;Von Garnier & Nicod, 2009;Nicod, Cochand & Dreher, 2000;Banchereau et al, 2000;Soloff & Barratt-Boyes, 2010;Mokhtar & Hussien, 2019;Zmrhal & Slama, 2020;Chakraborty et al, 2022). In humans, DCs are involved in resisting infections, protection against cancers, organ transplant rejections and in production of T-cell-dependent antibodies (Bodey, Bodey & Kaiser, 1997;Vervelde et al, 2013;Zanna et al, 2021;Yue, Zhang & Sun, 2022). DCs are found in lymphoid organs such as bone marrow and thymus, peripheral lymphoid tissues such as spleen and lymph nodes, in most nonlymphoid organs and in all epithelial surfaces that interface with external environments, e.g.…”
Section: Phagocytic Cells Involved In the Defence Of The Avian Lung (...mentioning
confidence: 99%
See 1 more Smart Citation